Retablo: Vindication of Andean Identity: Retablo: reivindicación de la identidad andina - Gutiérrez Gómez, Edgar (Revista de Filosofía, 2022)
The objective of the research is to analyze the intersubjective communication of the Andean identity, especially of Ayacucho, with the film Retablo [Altarpiece] that vindicates the inhabitants of the Peruvian highlands. The historical process of the Andean communities had its own way until the arrival of Spaniards. These communities remained for years, even today, stable in their organization preserving the order established by their founders. The social justice of the Andean communities apply punishment in public to those responsible for actions that go against the morality of the community. The film Retablo reflects and analyzes the experience of many peasants who cover up their spontaneity largely for fear of rejection. In the structuring of Andean communities, unrestricted respect for cultural individuality is encouraged. On the contrary, state is seen as alien, a powerful apparatus of discrimination compromised with the owners of the broad media, especially in political and social participation in pre- and post-electoral scenarios.